Opportunities and Challenges - Islamic Educational Thought in the Era of Digital E-Learning - Nadia Lekdjaa Djelloul Saiah (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2023)
This study seeks to identify Islamic pedagogical thinking in the light of e-education and to address the most important challenges that stand in the way of the proper educational construction of the individual, the family, society and the nation. Finally, we will draw a series of conclusions and recommendations, the most important of which will be: Digital education in today's era is no longer an option for learners, either to take it or to leave it, but to be called for by the needs of today. It must be accompanied by virtuous individual and social ethics, just as universal moral values govern acceptable moral behaviour in our